2014
DOI: 10.1007/s10562-014-1191-y
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Ultra-Thin ZnO Films Supported by Ag(111) and Cu(111): A Comparison to ZnO/Pt(111)

Abstract: Abstract.We studied structure and reactivity of ZnO(0001) ultrathin films grown on Ag (111) and Cu(111) single crystal surfaces. Structural characterization was carried out by scanning tunneling microscopy, Auger electron spectroscopy, low-energy electron diffraction, and temperature programmed desorption. The CO oxidation behavior of the films was studied at low temperature (450 K) at near atmospheric pressures using gas chromatography. For ZnO/Cu(111), it is shown that under reaction conditions ZnO readily m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
87
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 42 publications
10
87
1
1
Order By: Relevance
“…Different metals with their (111) orientations have been exploited as the growth substrates. Examples include Pd(111) [17], Pt(111) [18,19], Au(111) [20], Ag(111) [4,21,22], Cu(111) [22] and Brass(111) [23]. Prior to deposition, the surfaces of the metal substrates were cleaned by mechanical polishing [4] and by cycles of Ar + ion sputtering followed by annealing in UHV, at 1000 K for Pd [17], 750 K for Ag [4], 670 K [21] or 700 K for Au [20], and 1200 K for Pt [19].…”
Section: G-zno Growth Over a Metal Substratementioning
confidence: 99%
See 2 more Smart Citations
“…Different metals with their (111) orientations have been exploited as the growth substrates. Examples include Pd(111) [17], Pt(111) [18,19], Au(111) [20], Ag(111) [4,21,22], Cu(111) [22] and Brass(111) [23]. Prior to deposition, the surfaces of the metal substrates were cleaned by mechanical polishing [4] and by cycles of Ar + ion sputtering followed by annealing in UHV, at 1000 K for Pd [17], 750 K for Ag [4], 670 K [21] or 700 K for Au [20], and 1200 K for Pt [19].…”
Section: G-zno Growth Over a Metal Substratementioning
confidence: 99%
“…Prior to deposition, the surfaces of the metal substrates were cleaned by mechanical polishing [4] and by cycles of Ar + ion sputtering followed by annealing in UHV, at 1000 K for Pd [17], 750 K for Ag [4], 670 K [21] or 700 K for Au [20], and 1200 K for Pt [19]. In some cases [17][18][19]22], an annealing step was carried out in the presence of O 2 at high temperature (700-800 K) to remove residual carbon. To desorb the residual oxygen, the sample was then flashed to 1000 K in UHV.…”
Section: G-zno Growth Over a Metal Substratementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the CO oxidation is inhibited when ZnO films are grown on Ag(111). 13 Therefore, the local structural and electronic properties are of fundamental importance for a comprehensive understanding of the catalytic effect in ultrathin oxide materials. In addition, such a local structure of ultrathin oxide films is closely related with the microscopic growth mechanism.…”
Section: ■ Introductionmentioning
confidence: 99%
“…20 The CO oxidation behavior of ZnO films grown on Ag(111) and Cu(111) has also been investigated and it has been found that on Ag(111) the planar structure of the films is maintained in the course of the reaction. 21 Graphitic-like ZnO films and nanostructures on Ag(111) have then been characterized theoretically in various studies. 22,23 Ultrathin ZnO nanostructures have also been grown on Au(111) using reactive deposition at room temperature and characterized by X-ray photoelectron spectroscopy, STM, and DFT calculations.…”
Section: Introductionmentioning
confidence: 99%